De eletricista a iluminador cênico: os profissionais que trabalham nos bastidores da cena, formação e (in)visibilidade - Sidnei Honório Marques dos Santos (2022)
This dissertation analyzes how the professions of the Lighting Designer and the Theatre Electrician were delineated. To do so, we start from some premises extracted from its theoretical bases, which have already been defined and mapped by the specialized literature, as following: Light as Dramaturgy, Performativity of Light, Theatricality, Visibility and Visuality of the Scene. They had helped us as acess operators to the corpus of this research: the Lighting Design in the State of Minas Gerais (Brazil). Since the fundamental knowledge of the exercise of these two professions is, in most cases, from the beginning to the contemporary, transmitted from a master to his apprentice, the heat of day to day work, the research triggered an intimate relationship between professional trajectory and formation. We chose to address this topic with the aim of defining possible actions that give the professionals who work behind the scenes their due value, and a considerable part of the merit for the successful implementation of the staging. We thus contribute to the visibility and representativeness of this class. The modus operandi – whether of formation, professional trajectory or the (in)visibility of these professionals – came to light through a case study in the Brazil, in the Stage of Minas Gerais: the iluminator Jorge Luiz da Silva (in memoriam, 10/20/1955-03/23/2009).